(untitled) (Global Journal of Science Frontier Research, 2018)
Low use efficiencies of inorganic fertilizers coupled with their rising costs has diverted attention of farmers towards organic sources. Against this backdrop, a study was conducted in Matuu in Yatta subcounty, Machakos County, to evaluate the influence of tillage practices, cropping systems and organic inputs on soil nutrient status. The study was carried out between October 2012 to February 2013 short rains (SRS) and April-August 2013 long rainy seasons (LRS). ARandomized Complete Block Design with a split-split plot arrangement replicated three times was used where the main plots were the tillage practices (TP): Oxen plough (OP), Tied ridges (TR) and Furrows and Ridges (FR). The split-plots comprised the cropping systems (CS): Mono-cropping (MC), Intercropping (IC), and Crop rotation (CR) while split-split plots were organic inputs: Farmyard manure (FYM), Minjingu Rock Phosphate (MRP), combined MRP and FYM (MRP+FYM) plus the Control. The test crops were sorghum and sweet potatoes (Impomea batata) with Dolichos (Dolichos lablab) and chickpea (CicerarietinumL.) added either as intercrops or in rotation. Soil samples were taken randomly at 0-30 cm depth at the onset of the experiment and at maturity of test crop for soil (NPK and %OC) analysis. There was a significant (P≤0.05) high level ofK (1.91Cmol/+kg), available P (51.45 ppm), Total N (0.19%) and OC (2.19%), in combined TR, intercrop sorghum/chickpea with application of MRP+FYM during SRS of 2012 compared to the other treatment combinations.